Analisis Penerapan Upah Minimum Provinsi dan Tingkat Pendidikan Terhadap Penyerapan Tenaga Kerja Di Provinsi Kalimantan - Ariani; Muh. Irfandy Azis; Charitin Devi; Rista Kartika (Ekonomi dan Bisnis, 2025)
Purpose: This study aims to analyze the effect of provincial minimum wages and education levels on labor absorption in Kalimantan Province. Design/methodology/approach: The study used secondary data from 2019 to 2024 with a panel data regression method. The estimation was conducted using the Random Effect Model (REM) approach to examine the effect of independent variables on labor absorption. Findings: The results show that the provincial minimum wage does not have a significant effect on labor absorption, while the level of education has a significant effect on labor absorption. Simultaneously, the provincial minimum wage and education levels have a positive and significant effect on labor absorption as indicated by an increase in the number of workers absorbed in Kalimantan Province. Research limitations/implications: This study is limited to the period of 2019-2024 and only covers the Kalimantan region, so the results cannot be generalized to all regions in Indonesia. Further studies are recommended to expand the variables and coverage area in order to obtain a more comprehensive understanding. Practical implications: These findings emphasize the importance of establishing a balanced minimum wage policy and improving the quality of education and workforce skills as strategies to strengthen labor absorption and reduce unemployment rates in Kalimantan Province. Originality/value: This study provides empirical evidence by analyzing the effect of provincial minimum wages and education levels on labor absorption using cross-provincial panel data in Kalimantan from 2019–2024. The study contributes to the literature on regional labor markets, particularly in natural resource–based regions such as Kalimantan. Paper type: Research paper.   Keywords: Provincial Minimum Wages; Education Level; Labor Absorption; Kalimantan Province.